Design of Seamless Knitted Health Care Pants for Knee Arthritis Based on Grey Correlation Analysis (Journal of Fiber Bioengineering and Informatics, 2020)
As a common disease in the elderly, the research on knee arthritis is mostly clinical treatment, butthe research on functional health care pants for the daily health care of knee osteoarthritis patientsis less. In view of this phenomenon, this paper explores the function of the health pants through theinterviews of experts and the questionnaire survey of patients, and analyzes the weight of the functiondemand. Aiming at the five functional requirements with large weight, the fabric was screened, testedand analyzed by grey correlation degree. According to the analysis results, choose the fabric with betterfunction and choose different tissues according to different parts, so as to design a kind of health carepants for knee arthritis to meet the needs of health care and comfort.